Genome-Wide Analysis of the Trehalose-6-Phosphate Synthase Gene Family in Rose (Rosa chinensis) and Differential Expression under Heat Stress - Xiao-Ru Wei; Wu Ling; Yu-Wan Ma; Jiao-Lin Du; Fu-Xiang Cao; Hai-Xia Chen; Ji-Ren Chen; Yu-Fan Li (Horticulturae, 2022)
Trehalose and some members of the trehalose 6-phosphate synthase (TPS) gene family play important roles in response to abiotic stress in plants. However, no studies investigating the TPS gene in rose have been reported. In this study, the trehalose content in the stems and roots of Rosa chinensis was significantly increased under heat stress, and nine TPS family members were identified from the genome of R. chinensis. The R. chinensis TPS (RcTPS) family members could be divided into two subfamilies based on the structure and phylogenetic analysis. In this study, we found that segmental duplications contributed to the expansion of the RcTPS gene family, and the type II subfamily gene pairs RcTPS9–RcTPS10 and RcTPS7a–RcTPS7b were created by segmental duplication events. The type I subfamily RcTPS members contained 17 exons in the protein-coding region, whereas type II subfamily members only had 3 or 4 exons. Most cis-acting elements in the promoters of RcTPS members were related to plant hormones, especially ABA hormones. A phylogenetic tree of 78 TPS homologous amino acids from R. chinensis and another 7 species was constructed, which could be divided into 5 clades, and purity selection was observed to be the dominant evolutionary selection pressure. Under heat stress, except for RcTPS1b, the other eight RcTPS members were upregulated in the roots, stems, orleaves. The type II subfamily members RcTPS7a and RcTPS7b showed significantly high expression patterns in response to heat stress in all three tissues. Our findings indicate that RcTPS7a and RcTPS7b may play important roles in the heat tolerance of R. chinensis and are helpful for future functional studies of the two RcTPS members during heat stress.